Deconstructing the Downward Spiral: Anthology as Coherence in the Book of Judges - Hurlbert, Brandon M. (Journal of Biblical literature, 2024)
Many conceive of the shape of the book of Judges as a downward spiral with each leader getting worse, culminating in the horrific events of Judg 19-21. Proponents of this reading suggest that the judges can be evaluated by how closely they imitate their predecessors and the so-called judges cycle in Judg 2:11-19. In this article, I provide a historical survey to show that this interpretation originates during the literary turn in biblical studies and argues for a coherent literary reading in contrast to the source-critical approaches of the twentieth century. Since then, however, the downward spiral has become a cliché. Using eight tests, I argue that this reading is not substantiated through close textual analysis, and therefore Judges is better understood as a creatively curated anthology of stories set in a particular moral-literary world. The book demonstrates an ideological cohesion between the narratives but resists descriptions of linear progression along a particular theme (e.g., moral deterioration). Each of the main narratives (3:7-21:28) can be read on its own terms without the meaning being overdetermined by position or structure. Instead, Judges finds its narrative and ideological coherence through its anthology because each story is set within the same moral universe/narrative world.